Sequences in Adenovirus 5 E1A Gene that are Required for Transcriptional Activation, Enhancer Repression, and Oncogenic Transformation - Jelsma, Anthony (My University, 1998)
The E1A gene of adenovirus 5 carries out a number of functions in infection and oncogenic transformation, including the transcriptional activation of viral and cellular genes, the repression of transcriptional enhancers, and cooperation with the adenovirus E1B gene or with the ras oncegene to transform primary cells. The purpose of this work was to investigate the mechanism of action of E1A, by determining the regions of the proteins that are required for these functions. Deletion and point mutations were made in the region unique to the larger E1A mRNA, by exonuclease digestion and deletion loop mutagenesis respectively. These mutants and a series of mutants which delete sequences spanning the entire coding region, were examined for their effect on transcriptional activation, enhancer repression, and transformation. The region which, when deleted, rendered E1A defective for transcriptional activation was found to be confined to the region unique to the 13s mRNA and the beginning of exon 2. Mutations in three regions, all within the 12s exon 1, affected repression activity. The first two, the N terminal region of the protein, and a region, CR1, conserved between adenovirus serotypes, were essential for repression activity. The third region, at the end of exon 1 of the 12s mRNA, was probably only indirectly involved in repression. Deletions in three regions of exon 1 resulted in a loss of the transforming function of E1A. The first two corresponded to the regions required for repression, suggesting that enhancer repression is a component of transformation. The third region, containing CR2, also conserved between adenovirus serotypes, is functionally distinct from the other two and appeared to affect the morphology of the transformants. These two functions did not operate efficiently when present ion separate plasmids. The 13s unique region and exon 2 were not required for transformation but the loss of the transactivation function of E1A did result in an increased adhesiveness of the transformants.
Functional Domains in Adenovirus 5 E1A
Keywords: adenovirus; gene; transcription; repression; oncogenic; transform; enhance; activate